Bond strength of composite to dentin: effect of acid etching and laser irradiation through an uncured self-etch adhesive system - Castro, F. L. A.; Carvalho, J. G.; Andrade, M. F. [UNESP]; Saad, José Roberto Cury [UNESP]; Hebling, J. [UNESP]; Lizarelli, R. F. Z. (Iop Publishing Ltd, 2014)
This study evaluated the effect on micro-tensile bond strength (mu-TBS) of laser irradiation of etched/unetched dentin through an uncured self-etching adhesive. Dentinal surfaces were treated with Clearfil SE Bond Adhesive (CSE) either according to the manufacturer's instructions (CSE) or without applying the primer (CSE/NP). The dentin was irradiated through the uncured adhesive, using an Nd: YAG laser at 0.75 or 1 W power settings. The adhesive was cured, composite crowns were built up, and the teeth were sectioned into beams (0.49 mm(2)) to be stressed under tension. Data were analyzed using one-way ANOVA and Tukey statistics (alpha = 5%). Dentin of the fractured specimens and the interfaces of untested beams were observed under scanning electron microscopy (SEM). The results showed that non-etched irradiated surfaces presented higher mu-TBS than etched and irradiated surfaces (p < 0.05). Laser irradiation alone did not lead to differences in mu-TBS (p > 0.05). SEM showed solidification globules on the surfaces of the specimens. The interfaces were similar on irradiated and non-irradiated surfaces. Laser irradiation of dentin through the uncured adhesive did not lead to higher mu-TBS when compared to the suggested manufacturer's technique. However, this treatment brought benefits when performed on unetched dentin, since bond strengths were higher when compared to etched dentin.
Keywords: self-etching; adhesive resin; lasers; dentin; tensile bond strength